AUTOMATION OF HOLE MAKING PROCESS WITH IN-LINE HOLE CONFIGURATION - ahmad, egi (Universitas Majalengka, 2025)
One of the machining processes that is often used in the industrial world is the drilling process (hole making process). The hole making process can be done manually or automatically depending on the needs. In the manufacture of products with a low level of accuracy and small quantities, the manual process is very effective to use, but in the manufacture of products with a high level of accuracy and large quantities, the manual process is no longer effective to use. Therefore, a process is needed that works automatically so that the results of the work are as expected. Automatic control systems can be done using microcontrollers, computers, PLCs, or circuits consisting of control components. The control components that are often used are relays, timers and counters. This final project will discuss the performance of the drilling machine in making several holes in a row and applying it with a control system. The automatic control system is used to move the workpiece holder (vice) and the drilling machine. The control components used are relays, timers, counters and limit switches. These control components are used as controllers on the workpiece holder and drilling machine controllers.